Rethinking Bullying Awareness Among Adolescents: Gender Bias, Sociocultural Normalisation and School-Based Prevention - Hilman Nasyar Faidhullah Sholehudin; Eva Imania Eliasa; Afanin Halqim; Erna Widiyanti (Indonesian Journal of Islamic Educational Review, 2026)
Bullying is a social phenomenon that remains widespread among adolescents. The problem with bullying lies not only in its frequency but also in adolescents' lack of awareness about recognising and interpreting it as a form of violence. This study aims to examine differences in bullying awareness levels among adolescents based on gender and to re-evaluate the relevance of the male resilience vs. female sensitivity narrative. The study employs a quantitative approach using a survey design targeting adolescent. Data were analysed both descriptively and inferentially using the chi-square test to examine the relationship between gender and bullying awareness levels. The results indicate that the majority of adolescents fall into the low awareness category (60.0%), followed by the moderate category (39.4%), and only a small proportion fall into the high category (0.6%). Descriptively, females tended to have a higher proportion of low awareness compared to males. However, the results of the inferential test showed that there was no significant relationship between gender and the level of bullying awareness (p = 0.489; Cramer’s V = 0.094). These findings indicate that bullying awareness among adolescents cannot be adequately explained by gender constructs alone but is more influenced by contextual factors such as social normalisation and peer group dynamics. Consequently, bullying prevention interventions should be designed universally, emphasising the cultivation of critical awareness, empathy, and the courage to act, without relying on gender-stereotype-based approaches.